Preparo, caracterização e estudos das propriedades físico-químicas de complexos polieletrolíticos de N,N,N-trimetilquitosana/heparina obtidos em diferentes pHs para uso em liberação controlada de heparina - Martins, Alessandro Francisco (2011)
Chitosan (CT) and N,N,N-trimethyl chitosan (TMC) were complexed with heparin (HP) to obtain polyelectrolyte complexes (PECs). The PEC from CS/HP, labeled as PEC1, was obtained at pH 5 (PEC1-5). The PECs from TMC/HP, labeled as PEC2, were obtained at pHs 5, 8, 10 and 12 (PEC2-5, PEC2-8, PEC2-10 and PEC2-12, respectively). The formation of PEC2 in alkaline media became possible due to the quaternization of CT. The structures of PECs were characterized by FTIR and CP-MAS 13C NMR spectroscopies. There were significant differences in the spectra of CPMAS 13C NMR of PECs in relation to the precursors (CT, TMC and HP). For PEC2, the differences were attributed mainly to the high degree of quaternization (DQ = 59%) of TMC. Through CP-MAS 13C NMR the ratio of carbons bonded to not charged nitrogen atoms (C2) to the carbons bonded to positively charged atoms (Cω) at TMC were calculated for each of PEC2 ones. The spectra of CP-MAS 13C NMR of PEC2 also showed significant changes that were dependent on pH in which the PECs were prepared. Furthermore, the CP-MAS 13C NMR spectra of PEC2 obtained in alkaline medium showed greater similarity to the spectrum of CP-MAS 13C NMR of HP. This fact was related to greater effectiveness of complexation between HP and TMC in alkaline medium and to the consequent increase in the ratio of carbons C2 and Cω (C2/Cω) in the structure of TMC. C2 refer to carbons covalently bonded to sites N- monomethyl (NM) and N-dimethyl (ND) in a non-charged, while the carbon Cω is assigned to carbons covalently bonded to sites N-trimethyl (NT+) and N-monomethyl (NM+) positively charged. SEM images confirm a high density of pores, of different sizes and heterogeneously distributed, in the matrix of PEC2-8. Thermal stability of PEC2 was analyzed by Thermogravimetry (TGA) and Differential Scanning Calorimetry (DSC). Both techniques allowed finding that the thermal stability of PEC2 increase linearly with increasing pH of the solution of TMC used in the preparation of the materials. These factors were directly correlated with the ratio C2/Cω. Higher selfassembling of PEC2-8 in relation to the other PEC2 obtained in alkaline medium was observed through WAXS analysis. This was confirmed calculating the areas of P1 (2ϴ = 30,11°), P2 (2ϴ = 43,04°) and P3 (2ϴ = 54,91°) of PEC2 obtained at pH 5, 8, 10 and 12 compared to the same peaks that appear in the WAXS profile of the TMC. This ratified the pH 8 as the best condition for the strongest complexation between TMC and HP. In vitro studies of HP release confirmed that the PEC2-8 may have potential for specific delivering of HP on environments with pH conditions close to the intestinal one (pH 7,4), because it was possible to release from this PEC, in distilled water (pH ~ 6), approximately 4.2 mg L-1 and/or 420 UI kg-1 of HP in 7 hours of study.